Humanistic-Based Learning Management: Harmonizing Multiculturalism in Building An Inclusive Learning Environment - Nuryadin, Nuryadin; Salamah, Salamah; KMR, Galuh Nashrulloh; Norlaila, Norlaila (JURNAL AL-TANZIM, 2024)
This research aims to analyze humanistic-based learning management in building an inclusive learning environment at one of Banjarmasin's multicultural madrasa educational institutions. This research used a qualitative case study approach, where researchers conducted interviews with 12 informants, consisting of madrasah leaders, teachers, and students, using purposive sampling techniques. Observations were carried out on managerial and learning activities at the madrasah, while documentation was carried out to complete various needs to strengthen the results of interviews and observations. Data analysis starts with data collection, reduction, display, and conclusion. The research results show that multicultural-based inclusive policies first form humanistic learning management. Second, humanistic-based learning management is carried out through needs analysis, policy development, harmonization of multiculturalism, and an inclusive learning environment. Third, continuous monitoring and evaluation. The implications of this research emphasize the importance of an educational approach that prioritizes humanistic, inclusive, and sustainable aspects of creating a learning environment that supports the holistic development of students from various cultural backgrounds.